Arthroscopic Anterior Cruciate Ligament Repair Versus Autograft Anterior Cruciate Ligament Reconstruction: A Meta-Analysis of Comparative Studies - Pang, Long; Li, Pengcheng; Li, Tao; Li, Yinghao; Zhu, Jing; Tang, Xin (Frontiers in Surgery, 2022)
Purpose To compare the clinical outcomes of arthroscopic anterior cruciate ligament (ACL) repair and autograft ACL reconstruction for ACL ruptures. Methods PubMed, EMBASE, Scopus, Web of Science and The Cochrane Library were searched for relevant studies from 1 January 1990 to 21 March 2022. Two evaluators independently screened the literature, extracted data and assessed the methodological quality of the enrolled studies. Meta-analysis was conducted using RevMan 5.4 software. Results Ten studies with mean follow-up periods from 12 to 36 months were included. For 638 patients with ACL ruptures, arthroscopic ACL repair showed statistically comparable outcomes of failure (p = 0.18), complications (p = 0.29), reoperation other than revision (p = 0.78), Lysholm score (p = 0.78), Tegner score (p = 0.70), and satisfaction (p = 0.45) when compared with autograft ACL reconstruction. A significantly higher rate of hardware removal (p = 0.0008) but greater International Knee Documentation Committee (IKDC) score (p = 0.009) were found in the ACL repair group. The heterogeneity of the side-to-side difference of anterior tibial translation (ΔATT) was high (I2 = 80%). After the sensitivity analysis, the I2 decreased dramatically (I2 = 32%), and the knees with ACL repair showed significantly greater ΔATT (P = 0.04). Conclusion For proximal ACL ruptures, arthroscopic ACL repair showed similar clinical outcomes, and even better functional performance when compared to autograft ACL reconstruction. ACL repair has a higher rate of hardware removal, and might be related to greater asymptomatic knee laxity. More high-quality prospective trials are needed to confirm our findings.